Efficient photocatalytic H2 production using visible‐light irradiation and (CuAg)xIn2xZn2(1 − 2x)S2 photocatalysts with tunable band gaps. (10th February 2014) - Zhang, Guangshan; Zhang, Wen; Minakata, Daisuke; Wang, Peng; Chen, Yongsheng; Crittenden, John
SUMMARY The band structures of semiconductor photocatalysts fundamentally determine the photocatalytic activity and the H2 production from the visible‐light‐driven water‐splitting reaction. We synthesize a suite of multicomponent sulfide photocatalysts, (CuAg)xIn2xZn2(1 − 2x)S2 (0 ≤ x ≤ 0.5), with tunable band gaps and small crystallite sizes to produce H2 using visible‐light irradiation. The band gap of the photocatalysts decreases from 3.47 eV to 1.51 eV with the increasing x value. The (CuAg)0.15In0.3Zn1.4S2 (x = 0.15) photocatalyst yielded the highest photocatalytic activity for H2 production owing to the broad visible‐light absorption range and suitable conduction band potential. Under the optimized reaction conditions, the highest H2 production rate is 230 µmol m−2 h−1 with a visible‐light irradiation of 2.7 × 10−5 einstein cm−2 s−1, and the quantum yield reaches 12.8% at 420 ± 5 nm within 24 h. Furthermore, the photocatalytic H2 production is shown to strongly depend on their band structures, which vary with the elemental ratios and could be analyzed by the Nernst relation. Copyright © 2014 John Wiley & Sons, Ltd.